Time series pCO2 at a coastal mooring: Internal consistency, seasonal cycles, and interannual variability. (1st August 2017) - Reimer, Janet J.; Cai, Wei-Jun; Xue, Liang; Vargas, Rodrigo; Noakes, Scott; Hu, Xinping; Signorini, Sergio R.; Mathis, Jeremy T.; Feely, Richard A.; Sutton, Adrienne J.; Sabine, Christopher; Musielewicz, Sylvia; et al.
Abstract: Marine carbonate system monitoring programs often consist of multiple observational methods that include underway cruise data, moored autonomous time series, and discrete water bottle samples. Monitored parameters include all, or some of the following: partial pressure of CO2 of the water ( p CO2w ) and air, dissolved inorganic carbon (DIC), total alkalinity (TA), and pH. Any combination of at least two of the aforementioned parameters can be used to calculate the others. In this study at the Gray's Reef (GR) mooring in the South Atlantic Bight (SAB) we: examine the internal consistency of p CO2w from underway cruise, moored autonomous time series, and calculated from bottle samples (DIC-TA pairing); describe the seasonal to interannual p CO2w time series variability and air-sea flux ( F CO2 ), as well as describe the potential sources of p CO2w variability; and determine the source/sink for atmospheric p CO2 . Over the ~8.5 years of GR mooring time series, mooring-underway and mooring-bottle calculated- p CO2w strongly correlate with r -values > 0.90. p CO2w and F CO2 time series follow seasonal thermal patterns; however, seasonal non-thermal processes, such as terrestrial export, net biological production, and air-sea exchange also influence variability. The linear slope of time series p CO2w increases by 5.2 ± 1.4 µatm y −1 with F CO2 increasing 51–70 mmol m −2 y −1 . The net F CO2 sign can switch interannually with the magnitude varying greatly. Non-thermal p CO2w is also increasing over the time series, likely indicating that terrestrial export and net biological processes drive the long term p CO2w increase. Highlights: Mooring, underway, and discrete water samples CO2 is examined. High interannual CO2 variability on ocean margins could be due to freshwater inputs. Non-thermal processes likely contribute to increased CO2 on an ocean margin.